2022
DOI: 10.3329/aajbb.v7i1.59385
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of plankton community and physico-chemical parameters in wishpond, wishpond-aquaponics system and traditional fish pond

Abstract: This study was designed to determine the interrelationship between physico-chemical parameters and plankton community in three different aquaculture systems (wishpond, wishpond aquaponics and traditional fish pond). The water quality parameters, dissolve oxygen (DO), temperature, pH, ammonia, alkalinity and transparency were monitored and found within the recommended range. Different phytoplankton of four (4) different groups were observed where Chlorophyceae group was the most dominant (8.03±0.19) × 103 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…(Table 2). Hossain et al (2022) as they also found Chlorophyceae as the dominant one among the other groups.…”
mentioning
confidence: 88%
“…(Table 2). Hossain et al (2022) as they also found Chlorophyceae as the dominant one among the other groups.…”
mentioning
confidence: 88%